Meta-Analysis on the Effect of Zinc on Reducing Diarrhea Episode in Toddlers - Widayati, Purwika; Rahardjo, Setyo Sri; Widyaningsih, Vitri (Indonesian Journal of Medicine, 2019)
Background: Diarrhea is a major cause of mortality and morbidity in toddlers in the world. A number of studies have shown that zinc supplements can reduce the severity and duration of diarrhea in toddlers. This study aimed to examine the effectiveness of zinc on reducing diarrhea episode in toddlers.Subjects and Method: This was a meta-analysis conducted using PRISMA systematic guideline. Articles published between year 2000 and 2019 were selected from PubMed, Science Direct, and Springer Link databases. Six articles met the Randomized Controlled Trial (RCT) criteria. These studies were conducted in developing countries. A sample of 692 children divided into two groups of 348 zinc and 344 placebo. The data were analyzed by Review Manager (RevMan) 5.3 program. The results were assessed for Mean difference (MD) and the analysis was carried out for heterogeneity.Results: There was a high heterogeneity between experiments (I2 = 91%; p <0.001) so that Random Effects Model (REM) was used. Zinc administration reduced the duration of diarrhea 0.89 days faster than placebo, and it was statistically significant (MD= -0.89; 95% CI= -1.52 to -0.26; p= 0.006).Conclusion: Zinc supplementation is more effective than placebo in reducing the duration of diarrhea in children.Keywords: effectiveness, zinc, diarrhea, toddlers, meta analysisCorrespondence: Purwika Widayati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: purwika15@gmail.com. Mobile: 081231153131.Indonesian Journal of Medicine (2019), 4(2): 183-191https://doi.org/10.26911/theijmed.2019.04.02.12